Measurements of Total Hemispherical Emissivity of A508/A533B Alloy Steel. (3rd July 2019) - Al Zubaidi, Faten N.; Walton, Kyle L.; Tompson, Robert V.; Ghosh, Tushar K.; Loyalka, Sudarshan K.
Abstract: The total hemispherical emissivity of A508/A533B alloy steels was measured for conditions of interest in nuclear plant safety. The effect of long-term oxidation on the emissivity of A508/A533B was simulated by oxidizing test samples using a three-zone tube furnace at temperatures of 573 and 773 K. An apparatus built and operated in compliance with the American Society for Testing and Materials C835-06 testing standard was used to measure the total hemispherical emissivity for the following surface conditions: (1) mirror-like polished (unoxidized), (2) polished surface oxidized in air, (3) wire-cut electrical discharge machining (EDM), and (4) EDM-cut surface oxidized in air. The emissivity of polished (unoxidized) A508/A533B strips varied from 0.16 to 0.24 within the temperature range from 552 to 1180 K. Increasing the oxidation time of polished A508/A533B from 10 to 100 h at 573 K provided slight increase in emissivity, whereas increasing the oxidation temperature from 573 to 773 K for a 10-h duration provided over a threefold increase in emissivity. EDM-cut surfaces had an emissivity of 0.51 at 464 K to 0. 54 at 845 K due to the inherent roughness and the presence of a recast layer and possible oxidation layer. Oxidizing EDM-cut A508/A533B in air at 573 K increased the emissivity compared to the unoxidized EDM-cut A508/A533B, but no additional increase in emissivity occurred from 500- to 1000-h durations. Further oxidation of A508/A533B oxidized at 573 K for 1000 h for an additional 500 h at 773 K resulted in spallation of the oxide layer. The emissivity of the sample with loose oxide removed had similar emissivity for EDM-cut A508/A533B at 537 K.